PENGARUH EKSTRAK KULIT DUKU (LANCIUM DOMESTICUM CORR) TERHADAP KEMATIAN KUTU BUSUK (CIMEX HEMIPTERUS) - Darmadi Darmadi (Jurnal Penelitian Kesmasy, 2021)
Bed bugs (Cimex hemipterus) are a type of insect found in the wild. The impact of bed bug bites or Cimex can cause dermatitis and allergies. In general, efforts to control and eradicate bed bugs use synthetic insecticides. The use of synthetic insecticides is usually not environmentally friendly, therefore there is a need for other alternatives to replace synthetic insecticides. One type of plant that has the potential as a natural insecticide is the bark extract of duku (Lansium domesticum Corr.). The purpose of this study was to determine the effect of duku peel extract on bed bug mortality at concentrations of 5%, 10% and 15%. This study uses a laboratory experimental method with a post test only control group design. Based on the results of the study with three repetitions, the average bed bug mortality at a concentration of 5% was able to kill 5 tails within 5 minutes. At a concentration of 10% it was able to kill 5 tails in 3 minutes, while a concentration of 15% was able to kill 5 bed bugs in 2 minutes. The result of statistical test with Annova test is 0.012. These results show < p Alpha (0.05), meaning that there is an effect on mortality of cimex hemipterus using duku bark extract of various concentrations. The results of this study concluded that duku bark extract (Lansium domesticum Corr.) has the potential as a natural insecticide.